2023
DOI: 10.3389/fpsyt.2023.1179703
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and depressive symptoms among men who have sex with men in China: A cross-sectional study

Abstract: BackgroundWhile psychosocial problems and their related factors in men who have sex with men (MSM) have been well documented in developed countries, there are still not many studies addressing this issue in China and the results are inconsistent. This study aimed to assess the prevalence of loneliness and depressive symptoms among MSM, examine their associated factors, and investigate potential factors moderating the link between depressive symptoms and loneliness.MethodsA cross-sectional study was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Previous research has shown that MSM stigma is a stronger predictor of depression than stress in general: perceived stigma and enacted stigma were highly prevalent among 736 participants, and stigma was associated with a higher prevalence of depressive symptoms [16]. The results of a cross-sectional study of Chinese MSM show that discrimination and stigma play an important role in the development of depression [17]. The results of another study in Nanjing, China, showed that perceived stigma not only directly affects depressive symptoms but also indirectly affects depression through other factors [18].…”
Section: Introductionmentioning
confidence: 91%
“…Previous research has shown that MSM stigma is a stronger predictor of depression than stress in general: perceived stigma and enacted stigma were highly prevalent among 736 participants, and stigma was associated with a higher prevalence of depressive symptoms [16]. The results of a cross-sectional study of Chinese MSM show that discrimination and stigma play an important role in the development of depression [17]. The results of another study in Nanjing, China, showed that perceived stigma not only directly affects depressive symptoms but also indirectly affects depression through other factors [18].…”
Section: Introductionmentioning
confidence: 91%